On Measuring Fiscal Performance - Musgrave, R. A. (The Review of Economics and Statistics, 1964)
PpT HE purpose of this paper is to appraise the cyclical performance of fiscal policy over two recent cycles ranging from 1957-3 (peak) to 1960-2 (peak), and from 1960-2 to the first quarter of 1963. Also, an attempt is made to appraise the full employment adequacy of fiscal policy over this period. The exercise shows that grading, as always, is a delicate matter and that the results will differ depending on what formula is used. The effectiveness of fiscal policy is not easily measured. Obviously, it cannot be demonstrated by searching for a simple association between budget deficit and prosperity, nor can its ineffectiveness be proven by showing deficits to be associated with declines in GNP.1 What matters, first of all, are changes in budgetary position relative to changes in GNP. Moreover, a distinction must be drawn between the built-in effects of changes in GNP on changes in fiscal position, and the effects of discretionary changes in fiscal parameters on GNP. The former relation, which dominates the picture of the last decade, leads to the observed positive association between change in GNP and the level of budget surplus. This association in no way disproves the proposition that the built-in increase in deficit dampens the decline in GNP, just as the built-in increase in surplus dampens the rise. The effects of discretionary changes in fiscal parameters, in turn, should lead to a negative relation between changes in GNP and budget surplus, but this relationship involves lags and is not easily read from the data. Ultimately, the only satisfactory way of measuring the effects of budget policy on GNP during a past period is in terms of an econometric model which isolates fiscal factors. No such attempt will be made here. Rather, we shall compute various overall indices of fiscal performance, based on a more or less simplified multiplier model of fiscal policy effects, and address ourselves to certain conceptual problems which they pose. Our concern will be first with the contribution of fiscal policy to cylical stability, and then with measures of its full employment adequacy.